The girl who speaks bear - "Anderson, Sophie" (London; Usborne Publishing Ltd, 2019)
They call me Yanka the Bear, not because of where I was found - only a few people know about that. Found abandoned in a bear cave as a baby, Yanka has always wondered where she is from. She tries to ignore the strange whispers and looks from the villagers, wishing she were as strong on the inside as she is on the outside. But, when she has to flee her house, looking for answers about who she is, a journey far beyond one that she ever imagined begins - from icy rivers to smouldering mountains, meeting an ever-growing herd of extraordinary friends along the way
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Friendship Juvenile fiction